SOCIO-ECONOMIC IMPACT ASSESSMENT OF CLIMATE VARIABILITY IN FISHERIN AND TOURISM - Moreno Díaz, Mary Luz (2015)
The purpose of this article is to review the researches that have been developed to assessthe impacts of climate variability on fisheries and coastal tourism, in order to identifywhether there is an integral methodological framework to compare these methodologicalprocesses and to follow it for future ratings in these areas. Any methodological approachesthat integrate the different steps to be followed for developing the economic assessmentof different socio-economic and environmental impacts of climate change and climatevariability both at specific and globally level, were not found.